Pemberdayaan Tim Pendamping Keluarga untuk Penurunan Stunting - Nurfatimah, Nurfatimah; Longgupa, Lisda Widianti; Ramadhan, Kadar (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Reducing stunting rates is a national priority, with ambitious goals to optimize child nutrition. Lantojaya Village's Empowering Family Support Team program serves as one of the solutions to prevent the birth of stunted infants. This community engagement activity aims to engage Family Support Team members as agents of change at the village level and reduce stunting rates through a family-focused approach.The program was held at Lantojaya Village Hall on May 19, 2023, with 25 participants. This includes identifying high-risk families, training and mentoring team members, and working closely with village governments. Evaluation of the program revealed positive changes in the knowledge and skills of team members in Lantojaya Village and a reduction in stunting rates. The success of this program represents a major step forward in efforts to prevent stunting and improve the quality of life for targeted families. This work is expected to reduce stunting, improve family knowledge about nutrition, and strengthen community commitment to keeping children healthy.